Perceived destination competitiveness and response behavior: A test of mediation / Zaliha Zainuddin... [et al.] - Zainuddin, Zaliha; Mohd Radzi, Salleh; Mohd Zahari, Mohd Salehuddin; Azman Ong, Mohd Hanafi (Universiti Teknologi MARA, SelangorFaculty of Hotel and Tourism Management, Universiti Teknologi MARA Cawangan Selangor, 2020)
This study intends to investigate the effect of tourist satisfaction towards the relationship of perceived destination competitiveness and response behavior of tourists using 384 tourists who have visited Langkawi Island. By using the Structural Equation Modeling based on Partial Least Square (PLS-SEM) statistical analysis method, the result indicates that, tourist satisfaction gives a mediating effect towards the relationship of perceived destination competitiveness and response behavior